2004
DOI: 10.1007/s11099-005-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought on photosynthetic characteristics of flag leaves of a newly-developed super-high-yield rice hybrid

Abstract: We investigated responses of chloroplasts from flag leaves of a newly-developed super-high-yield rice (Oryza sativa L.) hybrid LiangYouPeiJiu (LYPJ) to water stress (withholding irrigation) during the grain-filling period. In the early stage of water stress (0-6 d) only the activity of Hill reaction was inhibited, whereas activities of photophosphorylation and Ca 2+ -ATPase, and ATP content were increased and peaked in the day 6 of withholding irrigation. In the late stage of water stress (6-12 d), the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…Thus, with decreasing RWC, the functions of PS2, PS1, and electron transport are largely maintained, even when P N is strongly inhibited. In contrast, water stress may result in damage to the O 2 evolving complex of PS2 (Canaani et al 1986, Toivonen andVidaver 1988) and to the PS2 reaction centres, RCs (Havaux et al 1987, He et al 1995, Chen et al 2004, Bertamini et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, with decreasing RWC, the functions of PS2, PS1, and electron transport are largely maintained, even when P N is strongly inhibited. In contrast, water stress may result in damage to the O 2 evolving complex of PS2 (Canaani et al 1986, Toivonen andVidaver 1988) and to the PS2 reaction centres, RCs (Havaux et al 1987, He et al 1995, Chen et al 2004, Bertamini et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…These small pieces were placed in a bottle with 4% glutaraldehyde buffer solution and the air was pumped out of the bottle with a syringe in order for leaves to become fully soaked in buffer solution, according to the method described by Chen et al (2004) with some modifications,. Leaves were fixed at 4 1C or over 24 h. They were then rinsed in phosphate buffer (pH 7.4) for 15 min and post-fixed in 5% OsO 4 at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Chonan et al (1977) examined changes in chloroplast ultrastructure during leaf senescence in rice plants, but no data are available, to our knowledge, about the chloroplast ultrastucture of new rice cultivars, although many high-yield cultivars have been developed in last 30 years. Some work in our laboratory has examined the high-yield cultivar in terms of photosynthesis, resistance to various stresses (Chen et al, 2004) and morphology showing that its type is similar to its paternal line 9311, an ideal plant type. Our previous data indicated that LYPJ shows greater resistance to stressors than do other rice cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…This hybrid has a higher water consumption and longer maturing period than traditional cultivars (Chen et al, 2004). Previous studies have investigated its photosynthetic properties under normal conditions (Zhang et al, 2010), under high temperature (Ou et al, 2005), under different nitrogen rates (Wang et al, 2012), and under enhanced ultraviolet-B radiation (Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%